KAPASITAS KELEMBAGAAN DALAM PENGEMBANGAN DESA WISATA DI DESA TOMPO BULU, KEC. BALOCCI, KAB. PANGKAJENE DAN KEPULAUAN - Sulmiah, Sulmiah; Nurhidayah, Nurhidayah; Guntur, Muhammad; Johansyah, Oky Nur Pratiwi (Jurnal Administrasi Negara, 2024)
This research aims to determine Institutional Capacity in the Development of Tourism Villages in Tompo Bulu Village, Balocci District, Pangkajene and Islands Regency and provide an in-depth understanding of how institutional capacity plays a role in developing tourist villages, as well as identifying strengths and weaknesses in existing institutional dimensions, so that can provide recommendations for future improvements. Apart from that, it can have a positive impact on the development of tourist villages, this research can also be a reference for local governments and related organizations in developing more effective policies and strategies to optimize the potential of tourist villages. This research uses a qualitative approach. Data collection was carried out through observation, interviews and documentation techniques. The data analysis technique used in this research is interactive data analysis through stages: data condensation, data presentation, and conclusion testing. The results of this research show that institutional capacity in developing tourist villages in Tompo Bulu Village, Balocci District, Pangkajene and Islands Regency based on the five dimensions measured is quite good in supporting the development of tourist villages. This is shown by the results of interviews with informants regarding the five dimensions measured to determine institutional capacity so that it can be concluded that values, norms and social practices are good. Then sufficient individuals, organizations and organizational networks. Meanwhile, public governance is still lacking.